Predicting Blast Vibrations More Conveniently than with the USBM Method - R. F. Favreau; Patrice Favreau (International Society of Explosives Engineers, 2015)
"A blast with explosives creates vibration waves in the zone around the blast.The prediction of the intensity of vibrations is important because people in the cinity demand that the vibrations do not disturb them, and society imposes limits on the vibrations. The U. S. Bureau of Mines (USBM) showed that the easurement of the particle velocity U predicts the risk of damage from vibrations. A currentapproach of blasters to monitor vibrations is to measure them with a seismograph at several distances S, and create a graph of U vs. S and the explosive charge “W” according to the equation U = K / (S / W)N where K and N are constants that depend on the blast method and the nature of the ground over the distance S. Though useful, this equation is empirical, and the results predicted from it are very variable, as shown by figure 1 which indicates that a prediction of U can deviate significantly from the actual value. Moreover, a minimum of two seismograph measurements at two values of S are required to establish the curve. However, here now exists another very convenient method to predict U; it is with the simulator Vibmas, which is based on the fundamental principles of how a blast reates vibrations. This simulator takes into account not only W but rather all the blast parameters, the type of explosive and the properties of the rock. Moreover, to establish the calculation of U as a function of S, only one seismograph measurement is required rather than two as for the USBM method. This last difference is important because it makes it easy to predict U not only as a function of S, but also as a function of the orientation of S. On the site this allows much safer control of the vibrations, and the use of larger explosive charges which reduce excavation costs. The article presents results from a field case at a hydroelectric project in Canada, where the deviation was very moderate. Use of this vibration simulator on the Web is very easy."